2008
DOI: 10.1128/jvi.02556-07
|View full text |Cite
|
Sign up to set email alerts
|

New Complex Recombinant Genotype of Hepatitis B Virus Identified in Vietnam

Abstract: Hepatitis B virus (HBV) infection is a global health problem.Approximately 350 million people worldwide are chronic carriers of the virus (12). Eight HBV genotypes from A to H are defined by a divergence in the entire nucleotide sequence of more than 8% (1,14,18,19,23). The prevalence and distribution of HBV genotypes vary geographically (6,8,9). Some genotypes have been split into subgroups. In particular, Asian strains of HBV (genotypes B and C) vary genetically and can be classified into various subgroups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
118
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(123 citation statements)
references
References 28 publications
2
118
1
2
Order By: Relevance
“…The same conclusion for the strains was reached by a later study using a new methodological approach (10). By providing neither additional information nor a new analytical approach, Huy et al (3) surprisingly conclude that their strain, with those previously reported, represent a new genotype.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…The same conclusion for the strains was reached by a later study using a new methodological approach (10). By providing neither additional information nor a new analytical approach, Huy et al (3) surprisingly conclude that their strain, with those previously reported, represent a new genotype.…”
supporting
confidence: 51%
“…Recently, Huy et al described a new hepatitis B virus (HBV) strain isolated in Vietnam (3) and claimed it to be a "new genotype," "HBV genotype I," with a complex recombination involving genotypes C, A, and G. We refute both claims.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Eight genotypes (HBV/A to H) have been identified, representing divergence of .8 % in complete genomes (Arauz-Ruiz et al, 2002;Norder et al, 1994;Stuyver et al, 2000). Two additional genotypes, I and J, have been proposed (Olinger et al, 2008;Tatematsu et al, 2009;Huy et al, 2008). There is diversity within genotypes, some genotypes being divided into subgenotypes (Norder et al, 2004).…”
mentioning
confidence: 99%